Proposal of public policies regarding the mental and emotional health of the population - Panait (Loghin) Claudia Daniela, (Technium Social Sciences Journal, 2020)
A percentage of 13% of EU citizens are affected, at some point in their life, by depression. Paradoxically, Romanians are among the happiest Europeans, despite constant economic difficulties. However, surveys show that people are increasingly worried, suffering from anxiety, depression and stress. A recent study shows that 20% of Romanians suffer from mental disorders. Most are adults who have problems in professional life, in society, in the family. Such patients are always sad, without desire for life, they are withdrawn, they do not want to socialize. Anxiety is the main disease suffered by Romanians and even people around the world. Romanians are afraid of the economic crisis, corruption, poverty, climate change, terrorist attacks, crime. The objective of the public policy proposal is to approach with priority the mental and emotional health of the people in Romania.